Aqualuz: a new solar disinfection device for treatment of cistern water - Magalhães, Jefferson Hannover Faustino (2022)
We conducted field, laboratory and modeling studies to evaluate the efficiency of a new solar disinfection (SODIS) device called Aqualuz for the removal of Escherichia coli (EC) from cistern water in the Brazilian semiarid, for different solar exposure–water temperature conditions. The results indicated EC contamination (100–300 MPN/100 mL) in all tests performed. As compared to the literature, lower exposure times (2.5–4.0 h) and solar radiations (250–410 W/m²) were sufficient for EC elimination. Then, assuming the complete-mix approach and first-order kinetics, it was possible to adjust EC decay rate constants (k) considering three different models: constant k-value, k as a function of water temperature and a new formulation for k as a function of both solar radiation and water temperature. All models performed well with normalized root mean squared logarithmic error (NRMSLE) lower than 20%, but the best fitting was obtained with the new approach. A new relationship between solar radiation and water temperature was also obtained, which allowed model simulations of EC decay for 34 municipalities in the Brazilian northeast, resulting in a color map for the region depicting the exposure periods of 1.8–5.6 h for reaching a 3-log reduction.